2019
DOI: 10.3126/janr.v2i1.26053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different concentrations of sucrose and citric acid on vase life of rose

Abstract: Vase life is the most important parameter to determine the quality of cut flower, however, due to highly perishable nature is always challenging to vase life. An experiment was conducted at Horticulture Lab, Prithu Technical College, Dangon 2018 in order to find out best concentration of sucrose and citric solution that enhances and prolongs the better flower quality and longevity. Experiment was laid out in completely randomize design (CRD) with nine treatments and three replication. Rose sticks were harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…In this work, our results focused on the significant positive responses of all recorded quality parameters when moonstone fresh cut roses were treated with S compared with NS holding solution. Pragya et al [ 28 ] and Young and Wan [ 43 ] reported that S provides a vital substrate for respiration as well as structural material and carbon skeletons for flower opening and mentioned that 2% S in the holding solution better regulated water uptake, water relations, and transpiration loss and improved the postharvest quality of cut roses, flower fresh weight, and flower opening and prolonged their vase life. It was found that S increased leaf photosynthetic pigments, chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids, and the anthocyanin content of fresh cut rose also improved the impact of cytokinin on the delay of floral senescence and decreased the effect of ethylene on prolonging flower vase life [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, our results focused on the significant positive responses of all recorded quality parameters when moonstone fresh cut roses were treated with S compared with NS holding solution. Pragya et al [ 28 ] and Young and Wan [ 43 ] reported that S provides a vital substrate for respiration as well as structural material and carbon skeletons for flower opening and mentioned that 2% S in the holding solution better regulated water uptake, water relations, and transpiration loss and improved the postharvest quality of cut roses, flower fresh weight, and flower opening and prolonged their vase life. It was found that S increased leaf photosynthetic pigments, chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids, and the anthocyanin content of fresh cut rose also improved the impact of cytokinin on the delay of floral senescence and decreased the effect of ethylene on prolonging flower vase life [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two holding solutions, with or with no sucrose (S and NS, respectively) at 20 g/L, were used supplemented with MWCNTs alone, MWCNTs combined with 75 ppm GA 3 as a novel nano anti-senescence agent composite and GA 3 at 75 ppm alone (MWCNTs, MWCNTs/GA 3 75 composites and GA 3 75, respectively) employed at different concentrations with S as holding solution as follow (T1= Control; distilled water, T2= MWCNTs 10, T3= MWCNTs 20, T4= MWCNTs 30, T5= MWCNTs 40, T6= MWCNTs 50, T7= GA 3 75, T8= MWCNTs 10/GA 3 75 composites, T9= MWCNTs 20/GA 3 75 composites, T10= MWCNTs 30/GA 3 75 composites, T11= MWCNTs 40/GA 3 75 composites, and T12= MWCNTs 50/GA 3 75 composites ppm) the same concentrations were used without S, a total of 24 treatments, all were used as pulsing treatments for 24 h, silver nitrate AgNO 3 (Macsen Laboratories Rajasthan, India) at 10 ppm was added to both holding solutions to eliminate microorganisms growth [ 28 ]. The initial pH of the holding and the pulsing solutions were 7 - 7.2 and 6.2 - 6.5 respectively, both were adjusted by drops of citric acid to 5.8 ± 0.1 using a pH meter (211 Hanna Instruments, Cluj-Napoca, Romania).…”
Section: Methodsmentioning
confidence: 99%
“…From the present experiment, it is evident that sucrose solution is effective in controlling transpiration loss of cut tuberoses. Earlier, Aryal et al (2019) observed that sucrose solution increased the vase life of roses by reducing transpiration loss and influencing water uptake. The high transpiration loss in the H 2 O 2 solution might be due to higher chemical stress and/or shortage of carbohydrates in the solutions, resulting in quicker wilting in this treatment when compared to others.…”
Section: Transpiration Lossmentioning
confidence: 95%
“…As a result, it is seen that sugar-containing solutions provide more solution intake in daily vase solution intake (Kumar and Deen, 2017). Aryal et al, (2019) and Kshirsagar et al, (2021) reported that sucrose-containing solutions promote water uptake in roses and decrease respiration and transpiration rate. In the study, it is thought that the excessive daily vase solution intake is evident in T8 and T11 applications and that similar results are obtained in studies on this subject due to the presence of sugar in the solutions.…”
Section: Daily Water Uptake (Dwu)mentioning
confidence: 99%